Orbital cellulitis and pyogenic meningitis rare sequelae after snake bite - Naik, Rupeshkumar (International Journal of Research in Medical Sciences, 2016)
The incidence of snake bite is underestimated. Worldwide around 2800 species of snakes are known out of which 375 species are venomous. Snake bite effects on nervous, cardiac, renal systems. A 10-year-old male boy was got admitted after five days treating with a local snake bite professional. On admission, he was treated with antibiotics for an infection. His cerebellum and most of the brain noted with streaks of pus. Here a case of intracranial complication following snake bite is reported.